Milk purchase and consumption patterns in peri-urban low-income households in Kenya - Muunda, Emmanuel; Mtimet, Nadhem; Bett, E.; Wanyoike, Francis N.; Alonso, Silvia (Frontiers Media, 2023)
Milk plays an important role in the growth and development of children. In Kenya, it is one of the most produced and consumed animal-sourced foods, but often consumed in small amounts among children of low-income families, especially in urban settings. The aim of the study was to identify household milk purchase and consumption patterns of milk, with emphasis on young children, as well as estimate key determinants of such patterns to identify areas of leverage to increase milk consumption. Results showed that 98% of households purchased unprocessed fresh milk at least once during the 7 days prior to the survey, while only 17% purchased packed pasteurized milk. Findings from the Ordinary Least Squares (OLS) model of purchase behavior suggest that the amount of unpacked milk purchased by households is positively and significantly related to household income, the number of children below the age of 4, and the budget of animal-sourced food. The price and quantities of pasteurized milk purchased were negatively related to the amount of unpacked milk purchased. Consumption patterns for children below the age of 4 showed that milk and dairy products are most commonly consumed as part of dishes than as individual products. Informal markets played a key role in meeting the milk needs of children, but consumption was below recommended amounts. The clear association of income and milk intake calls for efforts from the government to support the dairy sector with policies that promote the availability and affordability of milk, especially for a sector that feeds low-income families, as it is the case with the informal dairy markets.